(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Fishes are cheap sources of protein and are commonly reared in artificial pond in Nigeria. Bacterial infested fishes have been a serious public health concern. This study therefore aimed to determine antibiotic susceptibility of isolated fish bacteria in Akure metropolis and discovered various bacterial pathogens infecting Clarias gariepinus (African catfish). Bacteria were isolated from fish body parts after aseptically collecting 100 fish samples from ten hatcheries and ten water samples. Conventional biochemical testing and visual criteria were used to identify the isolates. The Kirby-Bauer disc diffusion method was used to test antibiotic susceptibility of chosen microorganisms. Salmonella spp., Enterobacter spp., Klebsiella spp., B. subtillis S. pneumonia, B. cerceus Shigella spp., S. macesens were all tested for susceptibility to four of the most regularly used antibiotics in Akure metropolis: Ciprofloxacin, Ampicilin, Chloramphenicol, and Tetracycline. Ciprofloxacin is resistant against Salmonella spp. and Enterobacter spp. Ciprofloxacin susceptibility is intermediate in Enterobacter spp. and Klebsiella spp., S. pneumoniae, B. cerces, Shigella spp., and S. macesens. Enterobacter spp, Klebsiella spp, and B. subtillis are vulnerable to Ampicillin, but Salmonella spp, S. pneumonia, B. cerces, Shigella spp, and S. macesens are resistant. At least five (5) of the eight antibiotics tested were effective against all isolates. Fish bacteria in Akure metropolis were susceptible to some antibiotics, while others had intermediate susceptibility, and all were resistant to tetracycline, which was the most commonly used antibiotic in all hatcheries sampled, according to the survey. Antibiotic resistance is the result of antibiotic abuse. This found resistance is most likely indigenous to those bacteria, implying that fish microorganisms from the research area have low levels of acquired antibiotic resistance. During one stage of production or another, all of the hatcheries sampled experienced mass mortality. The majority of them died as a result of antibiotic resistance, with up to 60% of them dying. Therefore, antibiotics should not be used in hatchery processing in order to control acute cases of bacterial infection in hatcheries without being hampered by antibiotic resistance, and to reduce the risk of spreading antibiotic-resistant germs to the human population through fish products.